Absence of abnormal vascular changes on prenatal imaging aids in differentiating simple uterine scar dehiscence from placenta accreta spectrum: a case series - Adu-Bredu, Theophilus K.; Owusu, Yaw Gyanteh; Owusu-Bempah, Atta; Collins, Sally L. (Frontiers in Reproductive Health, 2023)
Accurate prenatal discrimination between a simple, non-adherent uterine scar dehiscence with an underlying placenta and the severe end of the placenta accreta spectrum is problematic as the two can appear similar on prenatal imaging. This may lead to the false diagnosis of placenta accreta spectrum resulting obstetric anxiety, overtreatment and potential iatrogenic morbidity. Despite potential similarities in the etiology, the manifestation and management of these two conditions is very different. The prenatal sonographic features of seven confirmed cases of simple uterine scar dehiscence with an underlying placenta previa were examined. The common sonographic features found for scar dehiscence was a thinned myometrium (<1 mm) overlying a generally homogenous placenta and a placental bulge. There was absence of lacunae and features of hypervascularity including bridging vessels. Our findings suggest accurate discrimination between a simple scar dehiscence with the placenta underlying it and placenta accreta spectrum can be made on prenatal ultrasound if the placenta is carefully examined for the vascular features unique to PAS.